Vehicle dynamics influence on traffic safety in case of a certain route deceleration. (August 2019) - Oţăt, O V; Oţăt, V; Racilă, L; Geonea, I; Tutunea, D
Abstract: The present paper is aimed at determining the kinematic and dynamic parameters of a vehicle during braking on a road in alignment. Closely related to the determining the braking capability, we need to consider the key parameters that characterize the maximum braking capabilities of a vehicle, i.e. maximum deceleration, minimum braking space and minimum braking time. Hence, resorting to the ADAMS Car software platform, we carried out a case study to determine the kinematic and dynamic parameters of a vehicle in the braking situation on the road in alignment. The virtual modeling developed within our case study consisted of five full-vehicle analyses of the braking situation on a track in alignment. The initial speeds of the vehicle and the gearbox shift varied for each of five analyzed cases, while the rest of the input parameters did not change. The initial speeds considered were: 30 km/h, 50 km/h, 80 km/h, 100 km/h and 120 km/h. Following the numerical processing, we set out to determine the forces and moments at the wheel at the braking moment. The processing of the numerical results envisaged a comparative analysis of the vehicle kinematic and dynamic parameters for the five cases analyzed.